Characterization, identiﬁcation and location of voltage sags: review of state of art (2012)
This article presents a review of the state of the art of the characterization, identification and location of tension gaps. The methods presented are the product of different analyzes applied to the electromagnetic disturbance, specifically to the voltage and current waveforms, where attributes and descriptors are proposed based on the theory of electrical circuits, electromagnetic transients and knowledge of the phenomenon. the disturbances according to a certain characteristic of interest. A review is made of both basic characterizations and methodologies that integrate more complex classifiers and descriptors. Emphasis is placed on characterization methods, along with their attributes and descriptors, including their limitations and possible improvements. According to the level of development found in these studies, there is a need for new methodologies that integrate characterization modules, cause diagnosis, location, assessment and information and / or knowledge extraction modules, with the intention of guiding it to a tool for automatic disturbance management of the electrical system.